Nonsyntenic Genes Drive Tissue-Specific Dynamics of Differential, Nonadditive, and Allelic Expression Patterns in Maize Hybrids . Issue 2 (19th April 2016) - Baldauf, Jutta A.; Marcon, Caroline; Paschold, Anja; Hochholdinger, Frank
Abstract : Nonsyntenic genes are overrepresented among differential, nonadditive, and allelic expression patterns in root tissues of maize hybrids during the early developmental manifestation of heterosis. Abstract: Distantly related maize ( Zea mays ) inbred lines display an exceptional degree of genomic diversity. F1 progeny of such inbred lines are often more vigorous than their parents, a phenomenon known as heterosis. In this study, we investigated how the genetic divergence of the maize inbred lines B73 and Mo17 and their F1 hybrid progeny is reflected in differential, nonadditive, and allelic expression patterns in primary root tissues. In pairwise comparisons of the four genotypes, the number of differentially expressed genes between the two parental inbred lines significantly exceeded those of parent versus hybrid comparisons in all four tissues under analysis. No differentially expressed genes were detected between reciprocal hybrids, which share the same nuclear genome. Moreover, hundreds of nonadditive and allelic expression ratios that were different from the expression ratios of the parents were observed in the reciprocal hybrids. The overlap of both nonadditive and allelic expression patterns in the reciprocal hybrids significantly exceeded the expected values. For all studied types of expression - differential, nonadditive, and allelic - substantial tissue-specific plasticity was observed. Significantly, nonsyntenic genes that evolved after the last whole genome duplication of a maize progenitor from genes with synteny to sorghum ( Sorghum bicolor ) were highly overrepresented among differential, nonadditive, and allelic expression patterns compared with the fraction of these genes among all expressed genes. This observation underscores the role of nonsyntenic genes in shaping the transcriptomic landscape of maize hybrids during the early developmental manifestation of heterosis in root tissues of maize hybrids.